Serum creatinine to cystatin C ratio reflects preoperative and early postoperative walking ability in older patients with hip fracture. Issue 2 (15th February 2022) - Okubo, Naoki; Yoshida, Takashi; Tanaka, Kazuya; Okada, Naoya; Hosoi, Kunihiko; Ohara, Masato; Takahashi, Kenji
Abstract: Background: The sarcopenia index (SI), calculated as the ratio of serum creatinine to cystatin C levels, reflects skeletal muscle mass and strength. Patients with hip fracture (HF) and sarcopenia have poor functional outcomes, and many require long‐term care after surgery. We hypothesized that the SI can predict preoperative and early postoperative functional outcomes. Methods: Preoperative serum creatinine and cystatin C were measured to calculate the SI for patients with surgically treated HF ( n  = 130, mean age: 87.8 ± 6.9 years). Walking ability before and 2 weeks after surgery was assessed, and patients were dichotomized into independent and assistance groups. To assess the validity of the SI, we examined its correlation with the quality [computed tomography (CT) value] and quantity (cross‐sectional area) of the muscles around the hip on the non‐operated side, which were preoperatively measured using CT. Receiver operating characteristic (ROC) analysis was performed to evaluate the prognostic value of the SI. Results: The SI of the preoperative independent ( n  = 77) and assistance groups ( n  = 53) significantly differed (70.2 ± 12.4 and 60.1 ± 9.8, respectively, P  < 0.000001). At 2 weeks after surgery, the SI was significantly higher in the independent group ( n  = 31, 73.0 ± 14.9) than in the assistance group ( n  = 99, 64.0 ± 10.7, P  = 0.0003). In the preoperative independent group, 28 could walk independently after surgery (SI: 74.8 ± 14.0) while 49 required assistance (SI: 67.7 ± 10.6, P  = 0.01). For patients with femoral neck fracture (FNF), the SIs were significantly higher in the postoperative independent group (78.6 ± 15.7) than in the postoperative assistance group (63.2 ± 10.9, P  = 0.002). Logistic regression analysis showed that the odds ratio (95% confidence interval) of the SI for postoperative walking ability was 0.95 (0.91–0.99, P  = 0.03). The correlations of SIs with CT values and cross‐sectional areas were as follows: iliopsoas at the apex of the femoral head, r  = 0.40, P  < 0.001 and r  = 0.49, P  < 0.001, respectively; rectus femoris at the level of the lessor trochanter, r  = 0.26, P  = 0.007 and r  = 0.37, P  < 0.001, respectively. ROC analysis for predicting postoperative walking ability in preoperative independent patients with HF and FNF revealed areas under the curve (95% confidence interval) of 0.63 (0.50–0.76) and 0.80 (0.65–0.96), respectively. Conclusions: In patients with HF, the SI correlated with preoperative walking ability and could predict postoperative walking ability. Among patients who could walk independently before surgery, those with high SIs could walk independently early in the postoperative period. The SI is beneficial for estimating walking ability in patients with HF.